O Pacto pela Alfabetização e seus efeitos no trabalho docente da rede municipal de educação de Uberlândia/MG: processo de privatização e precarização da educação - Sobrinho, Sabrina Roberta (2024)
This research is linked to the Research Line State, Policies and Management in Education of the Postgraduate Program in Education (PPGED) of the Faculty of Education (FACED) of the Federal University of Uberlândia (UFU). Its object of investigation is the management of the literacy policy of the municipal education network of Uberlândia regarding the teaching materials of the Alfa e Beto and Educação Baseada em Evidências Institutes, the result of the agreement signed between the Municipality of Uberlândia, the Projeto de Vida Institute and the Raiar Institute. The aim is to analyze the effects of the Pact for Literacy Program on the organization of the pedagogical work of teachers working in the early years of elementary school in the municipality. The aim is to understand how this partnership reconfigures the work of teachers and schools and how the materials and methodologies used provide literacy for all the children in the municipality of Uberlândia, thus analyzing the Pact for Literacy. As far as methodological aspects are concerned, the research is based on the assumptions of qualitative research and, as procedures, develops bibliographical research, documentary analysis and interviews with teachers of the initial years of elementary school. The bibliographic research took place in the Brazilian Digital Library of Theses and Dissertations (BDTD), the Catalogue of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel Foundation (Capes), the UFU Repository, the Scientific Electronic Library Online (SciELO) Brazil and Capes Periodicals, with a time frame of 2012 to 2023. The documentary research analyzed legal provisions concerning literacy policy and its implementation strategies, considering privatization processes. Bardin's (2011) content analysis was used to analyze the semi-structured interviews. The analysis of literacy policies in the municipality of Uberlândia and the leading role of neoliberal theses that have driven privatized management models in the field of education, whether through the transfer of school management to Civil Society Organizations (CSOs), or through the insertion of pedagogical programs designed and produced by the private sector, transferring management itself within the Municipal Department of Education to the coordination of such groups. The conclusion is that this process affects the quality of education and the pedagogical autonomy of the schools, as well as devaluing the teaching staff by making them mere executors of externally defined materials without considering the reality of the institution and the students.